Novel, useful, and effective definitions for fuzzy linguistic hedges. (6th September 2006) - Chandramohan, Aarthi; Rao, M. V. C.
Abstract : The main emphasis of this paper is on fuzzy linguistic hedging, used to modify membership functions. This paper investigates the issues of obtaining new definitions for hedges which exceed the traditional definitions given by Zadeh (and others), particularly seeing that the effect of applying these hedges does not cross beyond the reasonable limits of membership values[ 0, 1 ] and is still meaningful from the point of view of magnitude of membership value and hence be really effective for an application. Some of the most commonly used hedges are presented, these hedges are very, positively, negatively, slightly more, and slightly less. The effects of these hedges on numeric examples are charted.